EVALUATION OF PREGNANCY ASSOCIATED HYPERTENSIVE STATES - N. A. Shakhbasova (Российский кардиологический журнал)
Aim. The main aim of current study was to investigate the significance and prevalence of the different risk factors for hypertension, caused by pregnancy. Material and methods. We evaluated different risk factors in 120 pregnant women with hypertensive states (main group) and in 50 healthy pregnant women at the same gestation period (control group). In pregnant women we evaluated the absence either presence of of pre-eclampsy risk factors: age, parity, hypertensive disorders during previous pregnancies, time gone since previous pregnancy, obesity, hypertension family anamnesis, inferlility, multiple precnancy, extragenital diseases. To calculate the relations between different qualitative signs the Pirson х used. Results. During the study it was revealed that in hypertension disorders the women had one risk factor in 30 (35,5%), two risk factors in 29 (34,1%), three and more risk factors in 26 (30,6%). It was found that in 30% of pregnants with pre-eclampsy and gestational hypertension there are no any risk factors. Most significant risk factors were first pregnancy and extragenital pathology. Combination of three and more risk factors is an anamnestic marker for higher risk of severe pre-eclampsy.Conclusion. The analysis of hypertension risk factors in pregnant women makes evidence-based the recognition of the high-risk group for pre-eclampsy. Further detailed diagnostic investigation of these women provides the opportunity to start a prophylaxy of hypertension disorders in pregnancy and to monitor the condition of clotting system, fetus condition and to improve the outcomes of a pregnancy. Absence of the risk factors does not decline a possibility of pre-eclampsy and requires the search for additional markers that would be early and pathogenetically proven signs.